The impact of masticatory dysfunction caused by occlusal disharmony on cognitive function - OU Yanzhen; LI Baosheng; CAI Qing; JIANG Jiayang; JIN Zhuohua; MENG Weiyan (口腔疾病防治, 2021)
As the world’s population ages, age-related cognitive decline and dementia are becoming important challenges for geriatric care. Despite the ongoing search for solutions to address cognitive decline, effective interventions have not yet been established. There is increasing evidence from clinical, epidemiological, and animal studies that masticatory dysfunction due to occlusal disharmony is a risk factor for cognitive decline and an increased incidence of dementia. The mechanisms may involve altered nutritional intake, decreased cerebral blood flow, chronic stress, and hippocampal morphological function. These findings suggest that maintaining and adequately restoring the entire masticatory system has a positive impact for the prevention of cognitive decline.